Source Control and Antibiotics in Intra-Abdominal Infections - Raffaele Bova; Giulia Griggio; Carlo Vallicelli; Giorgia Santandrea; Federico Coccolini; Luca Ansaloni; Massimo Sartelli; Vanni Agnoletti; Francesca Bravi; Fausto Catena (MDPI AG, 2024)
Intra-abdominal infections (IAIs) account for a major cause of morbidity and mortality, representing the second most common sepsis-related death with a hospital mortality of 23-38%. Prompt identification of sepsis source, appropriate resuscitation, and early treatment with the shortest delay possible are the cornerstones of management of IAIs and are associated with a more favorable clinical outcome. The aim of source control is to reduce microbial load by removing the infection source and it is achievable by using a wide range of procedures, such as definitive surgical removal of anatomic infectious foci, percutaneous drainage and toilette of infected collections, decompression, and debridement of infected and necrotic tissue or device removal, providing for the restoration of anatomy and function. Damage control surgery may be an option in selected septic patients. Intra-abdominal infections can be classified as uncomplicated or complicated causing localized or diffuse peritonitis. Early clinical evaluation is mandatory in order to optimize diagnostic testing and establish a therapeutic plan. Prognostic scores could serve as helpful tools in medical settings for evaluating both the seriousness and future outlook of a condition. The patient's conditions and the potential progression of the disease determine when to initiate source control. Patients can be classified into three groups based on disease severity, the origin of infection, and the patient's overall physical health, as well as any existing comorbidities. In recent decades, antibiotic resistance has become a global health threat caused by inappropriate antibiotic regimens, inadequate control measures, and infection prevention. The sepsis prevention and infection control protocols combined with optimizing antibiotic administration are crucial to improve outcome and should be encouraged in surgical departments. Antibiotic and antifungal regimens in patients with IAIs should be based on the resistance epidemiology, clinical conditions, and risk for multidrug resistance (MDR) and Candida spp. infections. Several challenges still exist regarding the effectiveness, timing, and patient stratification, as well as the procedures for source control. Antibiotic choice, optimal dosing, and duration of therapy are essential to achieve the best treatment. Promoting standard of care in the management of IAIs improves clinical outcomes worldwide. Further trials and stronger evidence are required to achieve optimal management with the least morbidity in the clinical care of critically ill patients with intra-abdominal sepsis.